Taxonomy and nomenclature of the recently published chlamydomonad genera Ostravamonas and Paludistella (Volvocales, Chlorophyceae) - Nakada, Takashi; Susanti, Hani (Phytotaxa, 2020)
A recently published chlamydomonad green algal genus, Paludistella H. Susanti, Mas. Yoshida, Tak. Nakayama, Nakada & M.M. Watanabe (2020: 72), was found to be superfluous as it originally included the type of Ostravamonas Barcytë & Hodač in Barcytë et al. (2020: 214). Here, the taxonomic and nomenclatural status under these generic names were examined based on morphological, phylogenetic, and ITS-2 secondary structure analyses, proposing two new combinations for P. asymmetrica H. Susanti, Mas. Yoshida, Tak. Nakayama, Nakada & M.M. Watanabe (2020: 76) and P. trianguloculus H. Susanti, Mas. Yoshida, Tak. Nakayama, Nakada & M.M. Watanabe (2020: 76) under Ostravamonas.